(untitled) (Journal of actual problems of jurisprudence, 2019)
In connection with the accession of Kazakhstan to the World Trade changed orientation in the agricultural policy, there is a need for priority development of medium and large-scale commodity production, capable of producing competitive products. Agricultural production in the country remains small-scale and this is one of the main reasons for its weak competitiveness. But among the peasants formed a different opinion. They believe that the unification of the rural consumer co-operative for them is not economically profitable. To reveal the nature of the problem is devoted to this article, by reviewing legislation to ensure that they impede or promote the unification of small-scale agricultural producers